2020
DOI: 10.3389/fimmu.2020.01350
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and HIV-1 Infection: Patterns of Chronic Antigen Exposure

Abstract: The main role of the human immune system is to eliminate cells presenting foreign antigens and abnormal patterns, while maintaining self-tolerance. However, when facing highly variable pathogens or antigens very similar to self-antigens, this system can fail in completely eliminating the anomalies, leading to the establishment of chronic pathologies. Prototypical examples of immune system defeat are cancer and Human Immunodeficiency Virus-1 (HIV-1) infection. In both conditions, the immune system is persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 290 publications
(393 reference statements)
0
12
0
Order By: Relevance
“…PD1 is a molecule expressed upon T-cell activation, which then acts as a checkpoint to prevent exaggerated T-cell activation through interacting with its ligand, PD-L1 or PD-L2 (45). In the past few decades, PD1expressing T cells have been well-established as an exhausted Tcell population with defective function generated during chronic viral infection and tumor development (46,47). Accordingly, targeting these cells by PD1 blockade has resulted in great clinical success in cancer immunotherapy for a variety of cancer types (48).…”
Section: Discussionmentioning
confidence: 99%
“…PD1 is a molecule expressed upon T-cell activation, which then acts as a checkpoint to prevent exaggerated T-cell activation through interacting with its ligand, PD-L1 or PD-L2 (45). In the past few decades, PD1expressing T cells have been well-established as an exhausted Tcell population with defective function generated during chronic viral infection and tumor development (46,47). Accordingly, targeting these cells by PD1 blockade has resulted in great clinical success in cancer immunotherapy for a variety of cancer types (48).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rates in breast cancer have been prominently decreased by immunotherapeutic strategies, but there still remains a need to identify key genes, especially those that could modulate the compound of the TME (3,38). Increasing evidence supports that immune cells within the TME could become a significant factor in predicting therapeutic efficacy and treatment outcomes (39)(40)(41)(42). In our study, we found that MKL1 was linked with the expression of different tumor-infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the transferred Irf4 ‐deficient CD8 + T cells barely differentiated into CD62L − CX3CR1 + cells when compared to those of control CD8 + T cells (Figure 4C,D). Inhibitory receptors are transiently expressed on functional effector T cells 25,26 . We found that Irf4 ‐deficient CD8 + T cells barely expressed inhibitory receptors PD‐1, TIM‐3 and LAG‐3 when compared to those of control CD8 + T cells (Figure ).…”
Section: Resultsmentioning
confidence: 85%
“…Inhibitory receptors are transiently expressed on functional effector T cells. 25,26 We found that Irf4-deficient CD8 + T cells barely expressed inhibitory receptors PD-1, TIM-3 and LAG-3 when compared to those of control CD8 + T cells ( Figure S2b-e). Taken together, IRF4 deficiency in CD8 + T cells abrogates their terminal effector differentiation in transplant recipients.…”
Section: Irf4 Deficiency In Cd8 + T Cells Abrogates Their Antigraft Fmentioning
confidence: 92%